Global Operations Strategy Fundamentals and Practice - Gong, Yeming. (Springer Texts in Business and Economics, 2013)
While many business schools are teaching Global Operations Strategy with self-made teaching materials, there are no such textbooks. Combining practical approaches with detailed theoretical underpinnings, this book provides theories, tools, frameworks, and techniques for global operations strategy, and brings real world perspectives to students and managers. Each chapter includes definition of key terms, introduction of fundamental theories, several short case examples, one long new case to explain the associated theories, and recommended further reading.